2021
DOI: 10.3390/coatings11080931
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanotubes Architectures for Solar Energy Conversion

Abstract: Electromagnetic light from the Sun is the largest source, and the cleanest energy available to us; extensive efforts have been dedicated to developing science and engineering solutions in order to avoid the use of fossil fuels. Solar energy transforms photons into electricity via the photovoltaic effect, generating about 20 GW of energy in the USA in 2020, sufficient to power about 17 million households. However, sunlight is erratic, and technologies to store electric energy storage are unwieldy and relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…For many years, TiO 2 has been widely used in solar cells, in photocatalysis, and in lithiumion batteries. [22][23][24][25][26] There are many different crystalline forms of TiO 2 (such as anatase, rutile, and bronze), but anatase and rutile TiO 2 are considered to be the most promising materials for solar cells and photocatalysts. More and more studies have found that when TiO 2 is used as rechargeable battery electrode material, it has better electrochemical cycle stability because of its small volume expansion and stable structure.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, TiO 2 has been widely used in solar cells, in photocatalysis, and in lithiumion batteries. [22][23][24][25][26] There are many different crystalline forms of TiO 2 (such as anatase, rutile, and bronze), but anatase and rutile TiO 2 are considered to be the most promising materials for solar cells and photocatalysts. More and more studies have found that when TiO 2 is used as rechargeable battery electrode material, it has better electrochemical cycle stability because of its small volume expansion and stable structure.…”
Section: Introductionmentioning
confidence: 99%
“…The process upscaling requires several optimization steps, and the elaborated route can only be performed at the laboratory scale and cannot be carried out on only a specific part of the substrate. In contrast to these limitations, laser technology offers rapid and easily scalable processing based on the interaction between the coherent, intense light of a particular wavelength with the material [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Additionally, the selection of the laser fluence and the environment in which the process is carried out (vacuum, ambient atmosphere, or ever water) can also be included into the group of important parameters affecting the final product [ 39 , 40 ] (see Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, the modification of TiO 2 NTs with laser radiation can be implemented using several different lasers which emit wavelengths from almost the whole spectrum. In most cases, the process leads to an amorphous-to-crystalline phase transition with a multi-fold increase in the measured photocurrent as well as a general enhancement of catalytic activity [ 35 , 40 , 41 , 42 , 43 ]. However, several drawbacks of the used treatment were also described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Anodic oxidation is a relatively simple and low-cost method that can obtain TiO 2 nanotubes with controllable geometry and self-organization under specific anodic oxidation conditions. TiO 2 nanotubes prepared through anodic oxidation have been widely used in photocatalysis, [6][7][8][9] solar cells, [10][11][12] sensors, [13][14][15] and biomedicine 16,17 owing to their remarkable photoelectrochemical properties and semiconducting properties.…”
mentioning
confidence: 99%